Preservation of fossils in the Šárka Formation (Darriwilian, Czech Republic) - Petr Kraft; Jana Bruthansová (Estonian Journal of Earth Sciences, 2023)
The Å Ã¡rka Formation is a well-known, fossiliferous Ordovician deposit in Bohemia. It has been targeted by fossil collectors since the 19th century due to the excellent preservation of many fossils. As a result, mainly well-preserved and interesting specimens have been deposited in collections. Many fragments, typical fossil accumulations but also complete specimens belonging to common taxa, have been ignored because they were considered poorly preserved compared to others. That is why some palaeoecological and taphonomical aspects of faunas are insufficiently represented in the existing collections.